Digital Mediation and Identity Negotiation in the Outer Baduy Community in the Social Media Era - A.S. Haris Sumadiria; Dian Wardiana Sjuchro; Ronny Yudhi Septa Priana (Mediator: Jurnal Komunikasi, 2025)
Digital transformation has reshaped the ways in which indigenous communities engage with the outside world, particularly in constructing and negotiating their cultural identities. This study explores how the Outer Baduy community in Banten employs social media as both a tool of digital mediation and a space for negotiating cultural identity in the midst of modern influences and cultural commodification. Adopting a qualitative approach through media ethnography, the research draws on in-depth interviews with four key informants: one traditional leader (jaro) and three local digital content creators, supplemented by field observations and social media content analysis. The findings reveal that younger generations strategically use social media to produce visual narratives highlighting local cultural practices, such as weaving, farming, and communal living. These digital expressions serve not only as a means of promoting cultural and economic activities but also as a medium for representing identity. At the same time, challenges emerge regarding the commodification of sacred values and the influence of algorithmic pressures, which shape both aesthetics and cultural meanings. In response, the community employs strategies of symbolic selection, guidance from traditional leaders, and digital literacy grounded in local wisdom to safeguard cultural integrity. This study underscores the importance of preserving the narrative sovereignty of indigenous communities within digital spaces and recommends fostering a communication ecosystem that remains attentive to local cultural values.